Temporal trend in quality indicators of diabetes care performance among persons with type 2 diabetes in primary care practice: a serial cross-sectional analytical study, 2013/14 to 2021/22 - Awiphan, Ratanaporn; Kowatcharakul, Woravut; Ruengorn, Chidchanok; Noppakun, Kajohnsak; Thavorn, Kednapa; Nochaiwong, Surapon (Frontiers in Endocrinology, 2024)
Background: Although the national-based policy implemented an initiative program to offer diabetes care management in Thailand, there are limited time trends of evidence to gauge whether the quality of diabetes care in primary care practice is improving. As such, we aimed to identify temporal trends in the quality of diabetes care performance among type 2 diabetes mellitus (T2DM) patients in primary care practice.: Using assembled patient-level data from a suburban community in northern Thailand, this serial retrospective cross-sectional analytical study obtained adult T2DM patients from nine consecutive fiscal years 2013/14 (n=976) to 2021/22 (n=1,242). Based on international and national guidelines recommended, nine quality indicators were examined, including smoking cessation, hemoglobin A1c monitoring, foot and eye examinations, albuminuria testing, statin prescription, angiotensin-converting enzyme inhibitor/angiotensin II receptor blocker (ACEI/ARB) prescription for chronic kidney disease (CKD)/albuminuria, and blood pressure and glycemic control. Rates and time trends achieved in each quality indicator performance were estimated. Differences in the rates of patients who met each quality indicator across reimbursement schemes were explored. Results: From 2013/14 to 2021/22, all quality indicators have increased over time (P for trend <0.05) except for smoking cessation, which remained steady. In 2021/22, only three out of nine quality indicators (i.e., smoking cessation, annual HbA1c monitoring, and annual foot examination) were successfully met at 70% or greater. Differences in quality indicators of diabetes performance were observed, particularly those under the Civil Servant Medical Benefit Scheme compared with other health insurance counterparts. For overall time trends analysis (compared with 2013/14), significant relative changes in the fiscal year 2021/22were found in the annual foot examination (adjusted 12.1% increase; P=0.048), annual albuminuria testing (adjusted 12.1% increase; P=0.048), and ACEI/ARB prescription for persons with CKD or albuminuria (adjusted 22.2% increase; P=0.025).Among adult T2DM patients from 2013/14 to 2021/22, overall quality indicators for diabetes performance have substantially improved over time. However, health inequity regarding diabetes care performance was found across different reimbursement schemes. Sustainable policy implementation and innovative strategies to narrow health inequity are warranted to optimize diabetes care in primary care practice.